METAPHORS AND SIMILES IN VAN GULIK’S SELF-TRANSLATION OF THE CHINESE MAZE MURDER - Aiqing Wang (Lexeme : Journal of Linguistics and Applied Linguistics, 2022)
A prolific and versatile Dutch writer, translator and orientalist Robert Hans van Gulik (1910-1967), aka 高罗佩 Gao Luopei, has composed a series of historical detective novels 大唐狄公案 Datang Digong An ‘Celebrated Cases of Judge Dee’, which concerns an illustrious district magistrate and statesman 狄仁杰 Di Renjie (630-704 AD), who competently investigates murder and corruption in Tang (618-907 AD) China. Upon publishing the debut work The Chinese Maze Murder (1951) in English, van Gulik renders it into a Chinese version entitled 狄仁杰奇案 Di Renjie Qian, which is the only self-translation by the author-cum-translator. In the Chinese version of The Chinese Maze Murder, the vast majority of metaphors and similes are translated by means of conversion and deletion, so they can be regarded as covert translations in the sense of House (1977, 2014).